Breaking the fibrinolytic speed limit with microwheel co‐delivery of tissue plasminogen activator and plasminogen - Disharoon, Dante; Trewyn, Brian G.; Herson, Paco S.; Marr, David W. M.; Neeves, Keith B. (Journal of thrombosis and haemostasis, 2022)
Background To reestablish blood flow in vessels occluded by clots, tissue plasminogen activator (tPA) can be used; however, its efficacy is limited by transport to and into a clot and by the depletion of its substrate, plasminogen. Objectives To overcome these rate limitations, a platform was designed to co‐deliver tPA and plasminogen based on microwheels (µwheels), wheel‐like assemblies of superparamagnetic colloidal beads that roll along surfaces at high speeds. Methods The biochemical speed limit was determined by measuring fibrinolysis of plasma clots at varying concentrations of tPA (10–800 nM) and plasminogen (1–6 µM). Biotinylated magnetic mesoporous silica nanoparticles were synthesized and bound to streptavidin‐coated superparamagnetic beads to make studded beads. Studded beads were loaded with plasminogen and tPA was immobilized on their surface. Plasminogen release and tPA activity were measured on the studded beads. Studded beads were assembled into µwheels with rotating magnetic fields and fibrinolysis of plasma clots was measured in a microfluidic device. Results The biochemical speed limit for plasma clots was ~15 µm/min. Plasminogen‐loaded, tPA‐immobilized µwheels lyse plasma clots at rates comparableto the biochemical speed limit. With the addition of a corkscrew motion, µwheels penetrate clots, thereby exceeding the biochemical speed limit (~20 µm/min) and achieving lysis rates 40‐fold higher than 50 nM tPA. Conclusions Co‐delivery of an immobilized enzyme and its substrate via a microbot capable of mechanical work has the potential to target and rapidly lyse clots that are inaccessible by mechanical thrombectomy devices or recalcitrant to systemic tPA delivery.